Формы эллиптических орбит и устойчивость газопылевых колец в прецессирующих галактиках - Антонов, В.А.; Железняк, О.А. (Кинематика и физика небесных тел, 1988)
Изучены свойства эллиптических орбит в поле тяготения прецессирующей галактики, представляемой в виде однородного сплюснутого сфероида. Получены три возможных типа орбит, по-разному наклоненных к экваториальной плоскости галактики. На основании вариационного принципа исследована их устойчивость. Показано, что одна из них устойчива по отношению к диссипативным факторам (вековая устойчивость), две другие—неустойчивы. Устойчивая орбита может физически реализоваться в прецессирующей галактике как стационарное газопылевое кольцо или диск с наклоном к экваториальной плоскости галактики. Characteristics of elliptic orbits in the gravitational field of a precessing galaxy assuming to be a homogeneous oblate spheroid are studied. Three possible types of orbits with different obliquities to the equatorial plane of the galaxy are found.
Basing on the variation principle the stability of elliptical orbits in the precessing galaxy is investigated. It is shown that one of three possible orbits is stable relative to dissipation factors (secular stability) and two others are unstable. A stable orbit may exist in the precessing galaxy as a stationary gas-dust ring or a disc that is inclined to the equatorial plane of the galaxy.